Effect of Nitrogen Sources on L-Dopa and Dopamine Production Using Citrobacter freundii (NRRL B-2643) - ÇAKMAK, Meltem; ÖZER, Dursun; KARATAS, Fikret; SAYDAM, Sinan (European Journal of Applied Sciences, 2022)
Microbial production of L-dopa and dopamine which is an important substrance for the treatment of Parkinson's disease were investigated by using Citrobacter freundii (NRRL B-2643). The effects of nitrogen source such as peptone, yeast extract, casein, soy protein, whey, ammonium sulfate on L-dopa and dopamine production were investigated and extracellular L-dopa and dopamine concentrations were determined by usign HPLC. Optimum nitrogen source concentrations were found to be (peptone 12.5 g/L, yeast extract 10.0 g/L, casein 0.1 g/L, soy protein 0.75g/L, whey 5% v/v and ammonium sulfate 1.0 g /L) for the production of L-dopa and dopamine. At this condition L-dopa and dopamine concentrations were found to be 342 and 467 mg/L, respectively. Although the experiments were continued for 60 hours, maximum production of L-dopa and dopamine concentration was reached at around the 30 th hour of the experiments.